Análisis del Crecimiento Urbano para la determinación de la Ocupación del Suelo en la parroquia Quinara del cantón y provincia de Loja - Rojas Tuzsa, Miguel Angel (2024)
The present research corresponds to the "Analysis of Urban Growth for the determination of Land Occupation in the Quinara parish, Loja canton and province", with the aim, not only of updating the information concerning the Land Use and Management Plans (PUGS as in its Spanish acronym), but also to analyze and evaluate the growth of the urban area of the Quinara parish; therefore the methodology approved by the Technical Council for Land Use and Management (CTUGS as in its Spanish acronym) was used to update the base and accumulated information since 2020, giving evidence of the increase in the number of urban properties registered until 2024, the increase coverage of drinking water, electricity and sewage services, likewise, due to the up-growing population, the implementation of a protection zone corresponding to the banks of streams and rivers, and areas with slopes greater than 30°; characterizing 3 central and 2 peripheral zones; furthermore, the increase in registered properties was determined, going from 306 to 354, where 206 are properties classified as occupied and 114 as vacant or empty properties, generating occupancy ranges that go from 0% to 51% at the most, having a rating from urban blocks in formation to complementation. To finally be able to identify that the south-east area is the most suitable for development, since it follows the trend of the main road, which generates greater accessibility, the guarantee to be provided with municipal utilities and the non-existence of covert areas due to withdrawal or pending margins that may risk the urbanization expansion. Keywords: C.T.U.G.S., expansion, occupation, territorial planning, P.U.G.S., Quinara, vacancy.